International Diversification and Performance in Family Firm: Exploring Nonlinear Relationships with the Governance Structure in an Emerging Economy - Espinosa-Mendez, C (Routledge, 2021)
In this study, we researched the relationship between international diversification and performance in family firms in an emerging economy. Likewise, from the perspective of the governance structure, we investigated non-linear relationships between business group membership, concentration of ownership as well as pyramid ownership with the performance of internationally diversified family firms. Considering a sample of 83 companies that have been listed on the Santiago de Chile Stock Exchange during the period between 2003 and 2013, we find an inverted U relationship between international diversification and performance; a U relationship between international diversification and performance in family firms; an inverted U relationship between the performance of internationalised family firms and affiliation to a business group; a U relationship between the performance of internationalised family firms and concentration of ownership; and a non-linear relationship in the inverted U form between the performance of internationalised family firms and high divergence between control and cash flow rights and U in the case of low divergence. © 2021 Asociación Española de Contabilidad y Administración de Empresas (AECA).